CO2 taxation and competitiveness of the German economy - an analysis with the macroeconomic information system (MIS). (1998) - Kemfert, Claudia; Pfaffenberger, Wolfgang
The German Federal Government is presently considering implementing an energy tax to reduce the CO2 emissions considerably by promoting energy conservation and substitution. This paper analyses macroeconomic consequences of introducing such a tax into the German Economy with the help of the Macroeconomic Information System (MIS). The Macroeconomic Information System was developed within the IKARUS (Instruments for Greenhouse Gas Reduction Strategies) context as a dynamic input-output model and an instrument for evaluating greenhouse gas emission reduction strategies and especially to check their macroeconomic consistency. MIS offers the possibility of analysing structural effects: on the one hand AEEI (autonomous energy efficiency) factors improve the energy efficiency, on the other hand MIS is based on a CES production function. Energy price variations and exogenous substitution elasticities induce the substitution process between capital and energy and between the individual types of energy themselves. Based on the 1989 national input-output table of the Federal Statistical Office, MIS divides the German economy into 30 sectors, i.e. 8 energy, 9 transport and 13 non-energy sectors. For the simulated target periods 2005 and 2020 macroeconomic simulation results as well as detailed information of the transport development, GNP, employment, energy consumption, CO2 emissions and the sectoral foreign trade development can be shown. In this paper the main interest lies with the evaluation of tax impacts on the competitiveness of the German economy. In particular, the substitution and structural effects induced by the CO2 tax will be analysed, considering also the sectoral foreign trade development of the most affected sectors.